The Influence of Marketing Mix With Digital Moderation on The Increase of Cash Waqf at The Waqf Nazhir Institution - Buchori, Nur Syamsudin; Firman, Firmansyah; Setiawan, Donny (Amwaluna: Jurnal Ekonomi dan Keuangan Syariah, 2025)
This study investigates whether digital marketing moderates the influence of marketing mix strategies-product, price, place, and promotion—on cash waqf contributions in the context of the “Berkah Wakaf” platform managed by the Indonesian Waqf Board (BWI). The research addresses the limited empirical understanding of how traditional marketing variables interact with digital tools in promoting Islamic philanthropic instruments such as waqf. Drawing on data from 225 respondents, including both current and prospective donors, the study applies a quantitative approach with structural equation modeling using Smart PLS. Results indicate that the marketing mix has no significant direct effect on cash waqf contributions. However, digital marketing shows a significant positive effect when applied independently. Its moderating effect, however, is statistically insignificant, suggesting that digital marketing does not strengthen the relationship between the marketing mix and waqf performance. These findings underscore the importance of digital trust and institutional credibility over conventional marketing efforts. The study contributes to the literature by highlighting the strategic role of digital engagement in enhancing cash waqf fundraising and offers practical insights for Islamic philanthropic institutions in adopting more targeted and technology-driven approaches.